The Anglo-Irish experience, 1680-1730 religion, identity and patriotism - Hayton, David 1949- (Boydell & Brewer, 2012)
The wars and revolutions of seventeenth-century Ireland established in power a ruling class of Protestant landowners whose culture and connexions were traditionally English, but whose interests and political loyalties were increasingly Irish. At first unsure of their self-image and ambivalent in their loyalties, they gradually became more confident and developed a distinctive notion of 'Irishness'. The Anglo-Irish Experience explores the religious, intellectual and political culture of this new elite during a period of change and adjustment. D.W. Hayton traces both the shifting sense of national identity characteristic of the period and the changing stereotype of the Irish in English popular literature - which did much to push the 'Anglo-Irish' to embrace their Irish heritage.